Pengaruh Pembelajaran Berdiferensiasi terhadap Motivasi Belajar dan Kemampuan Komunikasi Matematis Siswa SMPN 4 Tulungagung: The Influence of Differentiated Learning on Learning Motivation and Mathematical Communication Skills of Students at SMPN 4 Tulungagung - Sahputri, Rifda Guretno; Ilmi, Noraniza Bahrotul (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The results of observations at SMP Negeri 4 Tulungagung showed that students' learning motivation and mathematical communication skills were low. In this study, differentiated learning was applied as an effort to improve students' learning motivation and mathematical communication skills. The purpose of this study was to see whether there was an effect of differentiated learning on students' learning motivation and mathematical communication skills. The research method in this article is an experimental research method with a Pretest-Posttest Control Group Design research design. The research population was 306 students of class VII of SMP Negeri 4 Tulungagung with a sample of 34 students of class VII B as the control group and 34 students of class VII C as the experimental group. Sampling using cluster random sampling technique. The data obtained in this study were quantitative and qualitative data with research instruments including observation sheets, learning motivation questionnaires, mathematical communication ability test questions. Quantitative data analysis using the t-test. The results of data analysis show that learning motivation has a significance value of sig = 0.003, which means that there is an influence of differentiated learning on students' learning motivation, but on the other hand, the significance value of mathematical communication skills is sig = 0.277, which means that there is no influence of differentiated learning on the mathematical communication skills of class VII students at SMP Negeri 4 Tulungagung.